(untitled) (MMIT Proceedings, 2025)
This article analyzes the formation of the digital economy and the impact of information technologies on modern economic processes. The development of the digital economy leads to increased economic efficiency at the global and local levels, changes in market structures, and the emergence of new business models. The role of information technologies in automating economic processes, developing innovations, and increasing international competitiveness will also be studied. The study provides analytical data on the impact of information technologies on economic sectors and the possibilities of future growth.